Over-the-Counter Hearing Aids: A Case Study from the Community Pharmacy - Cippel, Adam (Seminars in Hearing, 2025)
In recent years, pharmacies have entered the over-the-counter (OTC) hearing aid market, providing an accessible alternative for individuals with hearing loss. This shift is driven by several key factors, including the limited availability of audiologists in many areas, particularly in rural or underserved regions. High-cost hearing aids can be a significant barrier for lower-income households. With the rising demand for affordable hearing solutions, pharmacies have emerged as a viable option for offering these devices, often at a fraction of the cost of traditional audiology services. By expanding access to hearing aids, pharmacies aim to address both the scarcity of specialized care and the financial constraints faced by many patients, making hearing health more attainable for a broader population. This article highlights how rural and elderly populations are often underserved in healthcare, with an emphasis on specialty services like audiology. It will demonstrate how a pharmacy recognized a disparity in the market and took action toward providing expanded patient care, unique to the usual pharmacy services we all know.
Keywords: OTC hearing aids; community health worker; expanded patient care